1987
DOI: 10.1002/1097-0142(19870315)59:6<1236::aid-cncr2820590634>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic index for malignant melanoma

Abstract: This report verifies the ability of a Prognostic Index (PI) to accurately predict 5-year survival rates for 879 Stage I cutaneous malignant melanoma (MM) patients seen at New York University Medical Center. The PI used in this study was first reported from Munich, West Germany, and is calculated from standard histologic sections by multiplying the MM thickness in millimeters (Breslow method) by the number of MM mitoses per square millimeter. A PI value of less than 19 versus greater than or equal to 19 was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Our study cohorts were comprised of prospectively-accrued, cutaneous melanoma patients at New York University Medical Center, enrolled in either the Melanoma Cooperative Group (MCG) (November 1972–November 1982) [12] or the Interdisciplinary Melanoma Cooperative Group (IMCG) (August 2002–December 2009) [13]. 18 patients were accrued at Bellevue Hospital, while the remaining patients were accrued at NYU Clinical Cancer Center.…”
Section: Methodsmentioning
confidence: 99%
“…Our study cohorts were comprised of prospectively-accrued, cutaneous melanoma patients at New York University Medical Center, enrolled in either the Melanoma Cooperative Group (MCG) (November 1972–November 1982) [12] or the Interdisciplinary Melanoma Cooperative Group (IMCG) (August 2002–December 2009) [13]. 18 patients were accrued at Bellevue Hospital, while the remaining patients were accrued at NYU Clinical Cancer Center.…”
Section: Methodsmentioning
confidence: 99%
“…[159][160][161] In the progression from primary to metastatic melanoma, the clinical tumor doubling time increases, and primary melanoma's tumor mitotic rate significantly correlates with decreasing survival. [123][124][125]133,[162][163][164][165][166][167] Ki-67 (ie, MIB-1) index, proliferating nuclear antigen index, S-phase fraction, and silver-stained nuclear organizing region counts all are reliable and widely used methods of measuring proliferative index (growth fraction), 168 and have been shown to be independent prognostic factors in small melanoma cohorts. [139][140][141][142] Moreover, cell-cycle regulators such as cyclins A and D3, p27 Kip1 , and p16 INK4 correlate with proliferative index markers and independently predict for prognosis in subsets of patients with melanoma (eg poor prognosis for cyclin D3 index [ 5% in superficial spreading melanoma).…”
Section: Potential Prognostic Molecular Markers In Primary Cutaneous mentioning
confidence: 99%
“…Koph et al 12 have reported survival rates of 23% and 85% with Pi (mitotic index × melanoma thickness) values of > 18 and < 18, respectively.…”
Section: Prognostic Index (Pi)mentioning
confidence: 99%